Omotic lexicon in its Afro-Asiatic setting VII: Further addenda to Omotic roots with *b- - Takács, Gábor (Lingua Posnaniensis, 2022)
The paper constitutes part of a long-range series aiming, step by step, to identify the inherited Afro-Asiatic stock in the etymologically little explored lexicon of the Omotic (West Ethiopia) branch of the Afro-Asiatic family displaying the least of shared traits among the six branches of this macrofamily, which suggests a most ancient Omotic desintegration reaching far back to the age of post-Natufian neolithic.